Marked Silence, Neo-Feudalistic Reactions and the Stabilized Moral Regime - The Current De- and Reformation of "the Sociale" - Fabian Kessl (Social Work and Society)
The German chancellor and leader of the German conservative party, Angela Merkel, said in an interview a few weeks ago:"Nobody could have imagined a few months ago to what extent we would be pushed into state intervention programs. Of course, Merkel spoke on, this intervention is not easy for anybody. Therefore, she recommended turning back to the former course as soon as possible"Â Â  (tagesschau.de, 11. März 2008, zit. nach Bildzeitungsinterview mit Angela Merkel, own translation). The worldwide celebrated new president of the United States, Barack Obama, said in an interview on CBS-News a few weeks before Merkel:"(...) there's no doubt that we have not been able yet to reset the confidence in the financial markets and in the consumer markets and among businesses that allow the economy to move forward in a strong way. And my job as president is gonna be to make sure that we restore that confidencee" (CBS News, 16. November 2008, Obama On Economic Crisis, Transition; http://www.cbsnews.com/stories/2008/11/16/60minutes/main4607893.shtml; Stand: 16. April 2009).